Supply Chain Finance: A supply chain-oriented perspective to mitigate commodity risk and pricing volatility. Issue 2 (March 2019) - Pellegrino, Roberta; Costantino, Nicola; Tauro, Danilo
Abstract: This study addresses the Supply Chain Finance challenge of Commodity Price Volatility (CPV) by adopting a supply chain-oriented perspective. In particular, the effectiveness of two Supply Chain Risk Management (SCRM) strategies in mitigating CPV, namely, Switching suppliers and Substituting Commodities, and the main factors that may affect their value, are investigated with a simulation analysis. A Real Option Valuation (ROV) model was developed and tested on real cases of CPV mitigation, as experienced by a large multinational company (Fortune 100) leader in the Fast Moving Consumer Goods (FMCG) industry. The results show the effectiveness of Switching suppliers and Substituting Commodities in mitigating CPV, highlighting that the convenience of adopting such strategies is strongly influenced by some specific conditions, like the relative values of the long-term prices of the commodities, the purchasing volume, and the sunk cost needed to build flexibility. Highlights: A supply chain-oriented perspective to Mitigate Commodity price volatility. Effectiveness of Supply Chain Risk Management strategies. Real Options for the evaluating Switching suppliers and Substituting Commodities . Factors influencing Supply Chain Risk Management strategies value.